Novel Treatment Strategies Targeting Myelin and Oligodendrocyte Dysfunction in Schizophrenia - Gouvêa-Junqueira, Danielle; Falvella, Ana Caroline Brambilla; Antunes, André Saraiva Leão Marcelo; Seabra, Gabriela; Brandão-Teles, Caroline; Martins-de-Souza, Daniel; Crunfli, Fernanda (Frontiers in Psychiatry, 2020)
Oligodendrocytes are the glial cells responsible for the formation of the myelin sheath around axons. During neurodevelopment, oligodendrocytes undergo maturation and differentiation, and later remyelination in adulthood. Abnormalities in these processes have been associated with behavioral and cognitive dysfunctions and the development of various mental illnesses like schizophrenia. Several studies have implicated oligodendrocyte dysfunction and myelin abnormalities in the disorder, together with altered expression of myelin-related genes, such as Olig2, CNP and NRG1. However, the molecular mechanisms subjacent of these alterations remain elusive. Schizophrenia is a severe, chronic psychiatric disorder affecting more than 23 million individuals worldwide and its symptoms usually appear at the beginning of adulthood. Currently, the major therapeutic strategy for schizophrenia relies on the use of antipsychotics. Despite their widespread use, the effects of antipsychotics on glial cells, especially oligodendrocytes, remain unclear Thus, is this review we highlight the current knowledge regarding oligodendrocyte dysfunction in schizophrenia, compiling data from (epi)genetic studies and up-to-date models to investigate the role of oligodendrocytes in the disorder. In addition, we examined potential targets currently investigated for the improvement of schizophrenia symptoms. Research in this area has been investigating potential beneficial compounds, including the D-amino acids D-Aspartate and D-Serine, that act as NMDA receptor agonists, modulating the glutamatergic signaling; the antioxidant N-acetylcysteine, a precursor in the synthesis of glutathione, protecting against the redox imbalance; as well as lithium, an inhibitor of GSK3β signaling, contributing to oligodendrocytes survival and functioning. In conclusion, there is strong evidence linking oligodendrocyte dysfunction to the development of schizophrenia. Hence, a better understanding of oligodendrocyte differentiation, as well as the effects of antipsychotic medication in these cells, could have potential implications for understanding the development of schizophrenia and finding new targets for drug development.